2024
DOI: 10.1039/d4ey00074a
|View full text |Cite
|
Sign up to set email alerts
|

Probing the active sites of oxide encapsulated electrocatalysts with controllable oxygen evolution selectivity

William D. H. Stinson,
Robert S. Stinson,
Jingjing Jin
et al.

Abstract: Electrocatalysts encapsulated by nanoscopic overlayers can control the rate of redox reactions at the outer surface of the overlayer or at the buried interface between the overlayer and the active...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
0
0
0
Order By: Relevance
“…SiO x overlayers on RuO x exhibit the most significant increase in OER selectivity despite a slight decrease in activity (Figure a). In contrast, TiO x encapsulated samples, while more active at a given overlayer thickness (Figure b), exhibit lower OER selectivity than SiO x , which we attribute to the TiO x overlayers being more permeable to Cl – and/or due to a higher electronic conductivity of TiO x , which can enable redox reactions to occur at the outer TiO x /electrolyte interface . Encapsulating Ru metal samples with SiO x and TiO x overlayers (Figure c,d) moderately improves stability, allowing for assessment of selectivity, which was not possible for bare Ru metal electrodes due to rapid corrosion.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…SiO x overlayers on RuO x exhibit the most significant increase in OER selectivity despite a slight decrease in activity (Figure a). In contrast, TiO x encapsulated samples, while more active at a given overlayer thickness (Figure b), exhibit lower OER selectivity than SiO x , which we attribute to the TiO x overlayers being more permeable to Cl – and/or due to a higher electronic conductivity of TiO x , which can enable redox reactions to occur at the outer TiO x /electrolyte interface . Encapsulating Ru metal samples with SiO x and TiO x overlayers (Figure c,d) moderately improves stability, allowing for assessment of selectivity, which was not possible for bare Ru metal electrodes due to rapid corrosion.…”
Section: Resultsmentioning
confidence: 97%
“…The 4 nm TiO x |RuO x sample was an exception, showing similar results to SiO x |RuO x , reaching 89.5% FE OER at 1.85 V vs RHE. Stinson et al found that TiO x overlayers with <4 nm thickness exhibited sufficient electronic conductivity to allow charge transport and reactions to occur at the outer surface of the electrode, while SiO x is more insulting. Similarly, this logic can be applied to explain the higher OER selectivity of SiO x |RuO x over TiO x |RuO x electrodes in this same thickness regime.…”
Section: Resultsmentioning
confidence: 99%